Municipal Solid Waste Management: Community Perspective on Sustainable Waste Management in Kota Kinabalu, Sabah - Kuinsin, Michelle Elana; Abdul Aziz, Nur Adila (Recent Trends in Civil Engineering and Built Environment, 2021)
A clean and beautiful environment is everyone’s desire. However, solid waste management becomes a significant challenge for most countries globally, including Malaysia, when urbanization occurs. The main objective of this study is to investigate the best sustainable approach in managing municipal solid waste (MSW) and the current practices of managing MSW in Sabah. The technique used to reach the study’s objectives, data collection, was using a qualitative method to distribute survey questions to the community that lives in Kota Kinabalu city. This study finding shows that the awareness among the communities is still low, and lack of governmental efforts to improve the MSW management. Therefore, to continually improvising Malaysia’s MSW management, each party should play its role. For future suggestions, Malaysia should consider using modern technology as a game-changer in waste management sustainability.